Resistance Band Shoulder Training and 15 Meter Archery Gains: Latihan Bahu dengan Resistance Band dan Peningkatan Jangkauan Panahan 15 Meter - Khumairo Hardiyanti Rukmana; Widi Arti (Academia Open, 2025)
General Background: Archery performance relies on upper extremity muscle strength, shoulder flexibility, and stable shooting mechanics to maintain accuracy. Specific Background: Weak arm strength and limited shoulder mobility often reduce drawing stability and shooting precision among archery athletes. Knowledge Gap: Evidence connecting resistance band shoulder training with measurable improvements in muscle strength, flexibility, and 15-meter archery scores remains limited. Aims: This study evaluated a six-week resistance band shoulder training program on arm muscle strength, shoulder flexibility, and shooting accuracy among university archery club members. Results: Following twelve training sessions, dominant arm strength increased from 20 kg to 21.5 kg, non-dominant arm strength improved from 17 kg to 18 kg, shoulder flexibility increased from 20 cm to 22.3 cm, and archery scores improved from 116 points to 124 points at a 15-meter distance. Novelty: This study combines clinical physical assessments with archery performance scoring to examine resistance band training within an archery conditioning program. Implications: Resistance band shoulder training can support physical readiness, joint mobility, and shooting consistency in structured archery training. Highlights: Progressive Elastic Exercise Produced Measurable Arm Force Development Across Dominant and Non-Dominant Sides. Combined Elevation Test Values Demonstrated Greater Joint Range During Upper Limb Movement. Shooting Score Progression Occurred After Structured Six-Week Conditioning Sessions. Keywords: Resistance Band Training, Shoulder Flexibility, Muscle Strength, Archery Accuracy, Sports Physiotherapy